Evaluation of the implementation of the dengue hemorrhagic fever eradication program (P2DBD) during the COVID-19 pandemic (study at the Sememi Health Center, Benowo district, Surabaya City) - Muhammad F. Dimjati Lusno; Ririh Yudhastuti; Setya Haksama; Jayanti D. Eka Sari; Milada M. Ravsanjanie; Abdul F. Farid; M. R. H. Farid; Febi Rahmadi (AOSIS, 2023)
Background: The Dengue Eradication Program is a government initiative to reduce dengue cases through preventive measures aimed at mosquitos. All activities in the various health sectors were restricted during the COVID-19 pandemic. The purpose of this study is to assess the Dengue Hemorrhagic Fever Eradication and Control program at the Sememi Health Center in Surabaya. Materials and Methods: This was a qualitative study with an evaluative approach. Key informants were identified using purposive sampling. The data was gathered through in-depth interviews and observations. The results were analyzed by evaluating the program's implementation using the system approach method. Results: It is well known that the program evaluation results are positive. The results of the input variables meet the minimum standards that have been established. The outcome of the process variables is less than ideal. Dengue prevention counseling, mosquito net eradication, monitoring, and evaluation activities were not carried out. All activities that make crowds impossible to carry out. The assessment of output variables is based on the number of larva-free days and dengue cases in the good category. Conclusion: The input and output variables are satisfactory in accordance with the government's policy provisions and should be maintained. To improve the program's effectiveness, process variables must be improved, specifically increasing the implementation of counseling activities related to dengue prevention, eradication of mosquito nets, and monitoring and evaluation activities.